recategorized by
966 views

1 Answer

0 votes
0 votes
Ans is option (C)

Substitute  $cotA=\frac{1}{tanA}$  in the above question, we get

$\frac{tan^{2}A}{tanA-1}+\frac{1}{tanA(1-tanA)}$

Simplifying further we get,    $\frac{1}{tanA-1}[tan^{2}A-\frac{1}{tanA}]$

$\Rightarrow$   $\frac{tan^{3}A-1}{(tanA-1)tanA}$

$\Rightarrow$   $\frac{(tanA-1)(tan^{2}A+tanA+1)}{(tanA-1)tanA}$     (using  $a^{3}-b^{3}=(a-b)(a^{2}+ab+b^{2})$)

$\Rightarrow$  $tanA+cotA+1$
Answer:

Related questions

1 votes
1 votes
1 answer
1
Lakshman Bhaiya asked Apr 1, 2020
826 views
If $\theta$ is an acute angle and $\tan\theta+\cot\theta =2$, Find the value of $\tan ^{7}\theta +\cot ^{7}\theta$.$-2$$1$$2$$0$
0 votes
0 votes
1 answer
2
1 votes
1 votes
1 answer
3
Lakshman Bhaiya asked Apr 1, 2020
921 views
If $cosec\theta-\sin\theta=1$ and $\sec\theta-\cos\theta=m$, then $l^{2}m^{2}(l^{2}+m^{2}+3)$ equals to:$1$$2$$2 \sin\theta$$\sin\theta \cos\theta$
0 votes
0 votes
1 answer
4
Lakshman Bhaiya asked Apr 3, 2020
700 views
If $ \ Sinx+Sin^{2} x=1$ then $ \ Cos^{8}x+ 2 \ Cos^{6} x+ \ Cos^{4} x$ equals to :$0$$-1$$1$$2$
1 votes
1 votes
1 answer
5
Lakshman Bhaiya asked Apr 3, 2020
635 views
$ \sin^{-1}\left [ \frac{3}{5} \right ] + \tan^{-1}\left [ \frac{1}{7} \right ]=$$\frac{\pi }{4}$$\frac{\pi }{2}$$ \cos^ {-1} \frac{4}{5} $$\pi$